Study Meta Analysis of Strategies and Utilization of Electronic Journals ( e - journals ) For Graduate Student University of Malang in Efforts Produce Internationally Reputed Scientific Publications - Ansor, Shokibul (Record and Library Journal, 2017)
Scientific publications in journals of international repute acts as a medium for self-actualization academics in the development of science internationally . Higher education institutions that have the quality of education , science and technology are good tend to have a high number of international publications . To produce scientific publications of high quality , must be supported by research and a source of reference quality . In an effort to improve the scientific publication of national repute academic environment . Malang State University. providing electronic information resources in the form of an electronic journal that comes from a variety of electronic information resources , in the hope utilized by students in an effort to increase scientific publication of international repute . The effort is also supported by a set of rules that requires that academic graduate students have a scientific publication of international repute as a graduation requirement